2022
DOI: 10.1007/s11250-022-03268-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of varying levels of purified condensed tannins on performance, blood profile, meat quality and methane emission in male Bapedi sheep fed grass hay and pellet-based diet

Abstract: This study determined the effect of purified condensed tannin inclusion levels in a diet on production, haematological indices, blood biochemical components, meat quality and methane emission by yearling indigenous male Bapedi sheep on a grass hay and sheep pellet-based diet in a 28-day trial. The diets contained similar (P > 0.05) nutrients but with different (P < 0.05) purified condensed tannin supplementation levels. A complete randomized design was used. Twenty-four yearling male Bapedi sheep were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
2
0
1
Order By: Relevance
“…Nutrient treatments (nitrate and lipid) that reduced methane emissions also did not adversely affect meat qualities such as tenderness, juiciness and so on [ 65 ]. Similary, tannins, known to have antioxidant properties, reduced methane emissions in sheep, but had no effect on Bapedi ram meat sensory attributes [ 66 ]. Mulberry supplementation has been reported to affect the meat quality.…”
Section: Association Between Beef Meat Quality and Methane Emissionmentioning
confidence: 99%
“…Nutrient treatments (nitrate and lipid) that reduced methane emissions also did not adversely affect meat qualities such as tenderness, juiciness and so on [ 65 ]. Similary, tannins, known to have antioxidant properties, reduced methane emissions in sheep, but had no effect on Bapedi ram meat sensory attributes [ 66 ]. Mulberry supplementation has been reported to affect the meat quality.…”
Section: Association Between Beef Meat Quality and Methane Emissionmentioning
confidence: 99%
“…However, Yagoubi et al [24] have previously reported that the dressing percentage and net meat percentage of Dorper and Small-Tailed Han F1 hybrid lambs were 49% and 80%, respectively, which were higher than those observed in this work. It was also found that the carcass weight decreased substantially when the sheep were fed diets containing tannins [25], and it was inferred that the thin carcass of sheep could be due to an improved protein content of carcass. Nevertheless Priolo et al [26] hypothesized that feeding tannins to lambs could lead to malnutrition of lambs.…”
Section: Effect Of Grape Residue Content On the Meat Productivity And...mentioning
confidence: 99%
“…Эффект подавления выделения этого газа за счет ВМР связан в основном с антимикробными свойствами ВМР (80). Растения производят множество вторичных соединений, среди которых большое внимание уделялось конденсированным дубильным веществам (81,82) и сапонинам (83). Три основных растительных соединения, эффективных для снижения выбросов метана in vitro, -это конденсированные дубильные вещества, сапонины и эфирные масла (84).…”
unclassified